Numerical simulation with hyperelastic constitutive model for high-performance multifilaments used in offshore mooring ropes - Daniel Magalhães da Cruz; Tales Luiz Popiolek Júnior; Marcelo de Ávila Barreto; Stephane Pires de Souza; Larissa Basei Zangalli; Aleones José da Cruz Júnior; Taline Carvalho Martins; Ana Lúcia Nazareth da Silva; Ivan Napoleão Bastos; Carlos Eduardo Marcos Guilherme (The Journal of Engineering and Exact Sciences)
The present study addresses the numerical simulation of the stress-strain behavior of synthetic multifilaments subjected to creep, fatigue cycles, and rupture. Understanding the mechanical properties of these materials is essential for various industrial applications, including technical textiles, ropes, cables, and composite materials. In this study, advanced simulation methods are employed using concepts from continuum mechanics and solid mechanics, coupled with a hyperelastic model. The simulated materials are high modulus polyester and polyethylene fibers for use in multifilament structures. Experimental tests were conducted to validate the simulation, and the simulation results were compared to the reference data to assess the quality of the numerical simulation. As a result, the numerical modeling shows capable of representing the constitutive behavior under creep, fatigue, and rupture solicitations. There was a certain difficulty in representing the behavior when many inelastic components were present in the fibers. Additionally, changes in curvature and concavity pose challenges that could potentially be addressed by other energy models integrated into the proposed code. These findings have significant implications in engineering sectors.